2010
DOI: 10.1177/0886260510362886
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relationship Between Child Maltreatment and Violent Delinquency: Using a Nationally Representative Sample

Abstract: This is an author-produced, peer-reviewed version of this article. The final, definitive version of this document can be found online at Journal of Interpersonal Violence, published by SAGE. Copyright restrictions may apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 29 publications
0
44
1
2
Order By: Relevance
“…However, one study showed that neglect in the first 2 years of life was more strongly associated with aggressive behaviour in childhood than either neglect in childhood or than physical abuse at any age [15]. More recently, Yun et al [8] analysed a nationally representative sample of adolescents from the United States and found that Pabuse in childhood was not related to subsequent self-reported violent crimes. They suggested that this result was ''unexpected'' and hypothesised that different mechanisms might explain the association between Pabuse and subsequent violent offending among disadvantaged youth at-risk for criminal offending and general population samples.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, one study showed that neglect in the first 2 years of life was more strongly associated with aggressive behaviour in childhood than either neglect in childhood or than physical abuse at any age [15]. More recently, Yun et al [8] analysed a nationally representative sample of adolescents from the United States and found that Pabuse in childhood was not related to subsequent self-reported violent crimes. They suggested that this result was ''unexpected'' and hypothesised that different mechanisms might explain the association between Pabuse and subsequent violent offending among disadvantaged youth at-risk for criminal offending and general population samples.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies, however, have failed to detect an association between maltreatment in childhood and subsequent criminal offending. For example, in a recent study of a nationally representative sample of adolescents in the United States physical abuse was not associated with subsequent violent delinquency [8]. Another study conducted in a large US city where rates of reports to child protective services were high, detected no association between maltreatment before age 4 and aggressive behaviour trajectories [9].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Children and adolescents who have been maltreated are more likely to engage in delinquent activities and more serious offending behaviors, compared to children and adolescents without a maltreatment history (Loeber & Farrington, 2001;Verrecchia, Fetzer, Lemmon, & Austin, 2010;Yun, Ball, & Lim, 2011). Due to the significant differences in outcomes of offending acts (e.g., arrest, conviction, delinquency adjudi cation), including whether official records or youthful offender selfreports were used, the link between maltreatment and delinquency may be underestimated (Maxfield, Weiler, & Widom, 2000).…”
Section: Maltreatment Victimizationmentioning
confidence: 99%
“…All three maltreatment types (physical abuse, sexual abuse, and neglect) have been linked to later antisocial behavior, violent crimes, and court involvement (Grogan-Kaylor, Ruffolo, Ortega, & Clarke, 2008; Lemmon, 2009;Yun et al, 2011), even in the presence of other risk factors (Loeber & Farrington, 2001;Widom & Maxfield, 2001). Research is clear that repeated maltreatment, no matter the type, has a key impact on youthful offending behavior (Arata, LanghinrichsenRohling, Bowers, & O'Brien, 2007).…”
Section: Maltreatment Victimizationmentioning
confidence: 99%